IMPLEMENTASI PERDA NOMOR 8 TAHUN 2016 TENTANG KESEJAHTERAAN LANJUT USIA DI KECAMATAN SALO KABUPATEN KAMPAR - Lisa Aprilia; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Implementation is seen broadly as having the meaning of implementing laws in which various actors, organizations, procedures and techniques work together to carry out policies in an effort to achieve the goals of policies or programs. Elderly according to the Law of the Republic of Indonesia Number 13 of 1998, namely men or women aged 60 years or more where a person has reached 60 years and over where his physical and cognitive abilities are decreasing. The purpose of this study is to find out how the implementation of Regional Regulation No. 8 of 2016 and to find out what are the inhibiting factors in the implementation of the Regional Regulation No. 8 of 2016. The theory used is the theory of Van Metter & Van Horn which affects the performance of public policy implementation. This research uses a type of qualitative research with a descriptive approach. The results of this study indicate that: First, the implementation of Regional Regulation No. 8 of 2016 has not run optimally because there are still some that have not been fulfilled from the program, three of the six indicators that the author uses are Standards and policy objectives, Resources, Inter-Organizational Communication and Implementing Activities . Second, the inhibiting factors are lack of communication, inappropriate targets and lack of budget. Keywords : Implemention, Welfare, Elderly